Pengembangan Media Pembelajaran E-Infografis Berbantuan Canva pada Mata Pelajaran Bahasa Indonesia Materi Pantun Kelas V SDN 2 Tiudan Kabupaten Tulungagung (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Indonesian language instruction regarding pantun (traditional Malay poetic forms) for fifth-grade students at SDN 2 Tiudan, Tulungagung Regency, currently lacks engaging and innovative learning media. This situation results in low student motivation and difficulties in comprehending the material. Therefore, there is a need for digital learning media that are both engaging and easy to understand. This study aims to develop a Canva-assisted digital E-Infographic learning medium for the pantun topic for fifth-grade elementary students and to determine its validity and practicality. The study employs the Research and Development (R&D) method using the ADDIE model, which encompasses the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observation, interviews, documentation, and validation questionnaires completed by media, subject matter, and language experts, as well as response questionnaires from teachers and students. The results indicate that the E-Infographic achieved validity scores of 94% from media experts, 93% from subject matter experts, and 96% from language experts, placing it in the "highly valid" category. Practicality tests yielded scores of 92% from students and 90% from teachers, placing it in the "highly practical" category. Thus, the Canva-assisted E-Infographic is deemed highly valid and highly practical for use as a learning medium for Indonesian language instruction on the subject of pantun